Patient-Centered Care: An Examination of Provider-Patient Communication Over Time - Leslie Riggle Miller; B. Mitchell Peck (SAGE Publishing, 2019)
Objective: To examine the quality of provider communication over time considering the increasing emphasis on patient-centered care (PCC). Patient-centered care has been shown to have a positive impact on health outcomes, care experiences, quality-of-life, as well as decreased costs. Given this emphasis, we expect that provider-patient communication has improved over time. Data Source: We collected primary data by self-report surveys between summer 2017 and fall 2018. Study Design: We use a quantitative retrospective cohort study of a national sample of 353 patients who had an ostomy surgery. Data Extraction Method: We measure provider communication from open-ended self-reports from patients of the number of stated inadequacies in their care. Principal Findings: Results show that the time since patients had their surgery is related to higher quality provider communication. That is, patients who had their surgery further back in time reported higher quality provider communication compared with patients who had their surgery performed more recently. Conclusion: Results suggest that the quality of provider communication has not improved even with an emphasis on PCC.